DESCARTES’ INFLUENCE ON PHENOMENOLOGY - Rasa Žiemytė (Problemos)
Descartes’ influence on phenomeno-logy is revealed in the context of other persons by whom E. Husserl was influenced. Some general ideas of Descartes and Husserl (which both resemble each other and are different, from each other) are compared to the phenomenological perspective. Cartesian philosophy is criticised in a Husserlian manner.